Perception of nursing professionals in relation to the use of playful techniques in urgency and emergency (Research, Society and Development, 2022)
In the context of pediatric urgent and emergency care, professionals in addition to technical capacity, a subjective and holistic view of child care is important. Therapeutic therapy is relevant in several contexts of the childhood phase, as it is through playful categorization that it will introduce a change in the child's perspective in the context of the hospital environment. Objective: to provide knowledge of playful techniques to nursing professionals in emergency care, encourage professionals to use playful techniques in care and promote continuing education to professionals in child care in the context of urgency and emergency. Methodology: Descriptive study, developed with 33 nursing care professionals (nurses and technicians) in day and night shifts in September in the emergency room of a State University Hospital in Paraná. Professional education was invited to a research, being used and to belong, to belong to the research question, in order to participate in order to participate in the research, in the context of urgency and emergency. of the institution. The results were analyzed using descriptive statistics from percentage calculations for each variable. The study on the importance of applying resources that professionals have knowledge about the use of playful strategies in this, but lack for its development, taking into account a reflection on the importance of applying strategic resources in child care in the context of urgency and emergency.